Green-Driver collection - Baker, Annabelle; Busby, William L., died 1919; Driver, William M., died 1943; Green, John Benjamin, died 1934.; Gresham, Pattie, 1882-1960.
Correspondence, topical files, financial records, printed matter, photographs, and other papers of businesswoman and church worker Pattie Gresham and her three husbands; insurance executive William L. Busby, Baptist minister and Masonic activist John Benjamin Green, and Baptist minister and grocery store owner William M. Driver. Documents African-American middle class, business, and church life in the American South during the Jim Crow era. Subjects include the activities of John Benjamin Green, especially his role as field secretary for the women's Masonic organization African American Heroines of Jericho, and of William M. Driver as an official of the Colored Knights of Phythias, also known as the Knights of Pythias of North America, South America, Europe, Asia, Africa and Australia. Miscellaneous items include Gresham's Duval County, Fla., 1938 voter registration certificate; business cards for her Africana Beauty Parlor in Jacksonville, Fla.; and her Cobb County, Ga., "pistol toters' license from 1920. Correspondents include Viktor Lowenfeld.
Includes correspondence and miscellaneous papers of artist Annabelle Baker whose education at Hampton Institute, Hampton, Va., Gresham sponsored during the early 1940s, relating chiefly to the controversy at the school concerning Baker's pioneering "natural" hairstyle. Also includes a brochure and prospectus published by African-American inventor and automobile manufacturer L.A. Headen's Headen Motor Company.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Headen, L. A; Lowenfeld, Viktor -- Correspondence; Driver family; Green family; Africana Beauty Parlor; Hampton Institute -- Students; Headen Motor Company; Knights of Pythias of North America, South America, Europe, Asia, Africa and Australia; African American business enterprises; African American business enterprises -- Southern States; African American Heroines of Jericho; African American women -- Societies and clubs; African Americans -- Social life and customs; African Americans -- Societies, etc; African Americans -- Southern States; African Americans -- Segregation -- Southern States; Automobile industry and trade -- United States; Baptists -- Southern States; Beauty shops -- Florida -- Jacksonville; Firearms -- Licenses -- Georgia -- Cobb County; Freemasonry; Hairdressing of African Americans; Voter registration -- Florida -- Duval County; Southern States -- History -- 1865-1951.; Southern States -- Race relations; Southern States -- Social life and customs